Pemikiran Teologis Abū Ḥanīfah tentang Irjā' dan Shafā'ah - Agus Aditoni (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article deals with the theological thought of Abū Ḥanīfah on the concepts of irjā' and shafā'ah. On the concept of irjā', Abū Ḥanīfah fully returns the legitimacy of 'Uthmān b. 'Affān as the third caliph and the superiority of 'Alī b. Abī Tālib merely to the authority of Allah. This concept rejects the Khariji doctrine on the expulsion of the wrong doers (sinful people) from the Muslim community, a rejection which implies that 'Uthmān is a legally accepted caliph. This concept also rejects the early Shī'ī doctrine on the superiority of 'Alī, and ranks al-Khulafā' al-Rāshidūn (the rightly guided caliphs) in accordance with their advantages and historical chronology. On the concept of shafā'ah, Abū Ḥanīfah believes it as something that will happen on the Day of Judgment. The followers of the Prophet Muhammad must fulfill twelve requirements if they wish to receive shafā'ah from the Prophet. To Abū Ḥanīfah, the Prophet's shafā'ah is certain for every Muslim although he/she committed great sin during his/her life except shirk bi Allah.